Cooperative Design, Visualization, and Engineering 5th International Conference, CDVE 2008 Calvià, Mallorca, Spain, September 21-25, 2008 Proceedings - Luo, Yuhua (Information Systems and Applications, incl. Internet/Web, and HCI, 2008)
This book constitutes the refereed proceedings of the 5th International Conference on Cooperative Design, Visualization, and Engineering, CDVE 2008, held in Calvià, Mallorca, Spain, in September 2008. The 45 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers cover all current issues in cooperative design, visualization, and engineering, ranging from theoretical and methodological topics to various systems and frameworks to applications in a variety of fields. The papers are organized in topical segments on cooperative design, cooperative visualization, cooperative engineering, cooperative applications, as well as basic theories, methods and technologies that support CDVE.